Exposure‐Exposure Relationship of Tocilizumab, an Anti–IL‐6 Receptor Monoclonal Antibody, in a Large Population of Patients With Rheumatoid Arthritis. (22nd February 2013) - Levi, Micha; Grange, Susan; Frey, Nicolas
Abstract Relationships between tocilizumab exposure and response were evaluated using data from 4 phase III studies. Increased tocilizumab exposure was associated with improvements in Disease Activity Score using 28 joints (DAS28) and American College of Rheumatology (ACR) criteria and with a decrease in inflammation markers. A population pharmacokinetic/pharmacodynamic (PKPD) model was developed to describe data from 2 studies. An indirect‐response model with a sigmoid Emax (maximal drug effect) inhibitory drug effect on DAS28 "production" rate adequately described the relationship between tocilizumab concentration and DAS28. Mean minimum serum tocilizumab concentration at steady state was greater than the EC50 (concentration at which 50% of Emax on DAS28 is reached) with the 8‐mg/kg dose but not with the 4‐mg/kgdose. Simulations within a large rheumatoid arthritis (RA) population showed that DAS remission rates were 38% for 8 mg/kg and 24% for 4 mg/kg. Tocilizumab was more potent in RA patients with higher baseline interleukin‐6 levels, but this effect was not clinically significant. Other covariates (eg, presence of neutralizing antitocilizumab antibodies) did not demonstrate a clinically meaningful effect on tocilizumab DAS28 dose‐response relationships. These data support clinical observations that tocilizumab 8 mg/kg is more effective than 4 mg/kg in reducing disease activity.